The Encyclopedia of the Horse - Hartley Edwards, Elwyn, 1927-2007; Photography by Langrish, Bob and Houghton, Kit (New York DK, 2012)
Get up close to 150 of the world's most famous horse and pony breeds and find out what makes each one special. Topics also include: the evolution of these amazing creatures, from their origins to their contribution to our civilisation; the latest on farriers, feeding, management, behaviour, training techniques and equipment; and the latest trends in equestrian sports, from dressage to horse trials
Include Color Illustration and Index
Keywords: Horses -- Horse breeds -- Horsemanship